Implementasi Pembelajaran Modular Berbasis Komputer meningkatkan Kompetensi Sistem Informasi Akuntansi Siswa Pelajaran Spreadsheet - Rhady Dzulfanaldy Harminal; Sasa S Suratman; Tri Sabaningsih; Ifa Hanifa; Alis Marlina (Jurnal Edukasi (Ekonomi, Pendidikan dan Akuntansi), 2026)
This study was motivated by the limited competence of students in preparing spreadsheet-based accounting cycles due to the lack of adequate learning materials and the limited effectiveness of printed modules in the learning process. This study aimed to examine the implementation of computer-based modular learning and its effect on improving students’ competence in Accounting Information Systems through the preparation of spreadsheet-based accounting cycles. A quantitative approach was employed using a quasi-experimental method with a Non-Equivalent Control Group Design. The study involved two groups: an experimental class that received treatment using digital modules and a control class that used printed modules. Data were collected through observation, pre-tests, and post-tests, while data analysis involved normality tests, homogeneity tests, t-tests, and gain analysis. The results showed that there was no significant difference in the initial abilities of the experimental and control classes. However, the post-test results revealed a significant difference, with a significance value of 0.001 < 0.05. The experimental class demonstrated a greater improvement in competence than the control class, with a gain score of 0.72, categorized as high. The observation results also indicated that computer-based modular learning encouraged students’ active participation and independence. Therefore, computer-based modular learning is effective in improving students’ competence in preparing spreadsheet-based accounting cycles